2016
DOI: 10.1007/s12250-016-3889-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cell culture models for investigating human viruses

Abstract: Three-dimensional (3D) culture models are physiologically relevant, as they provide reproducible results, experimental flexibility and can be adapted for high-throughput experiments. Moreover, these models bridge the gap between traditional two-dimensional (2D) monolayer cultures and animal models. 3D culture systems have significantly advanced basic cell science and tissue engineering, especially in the fields of cell biology and physiology, stem cell research, regenerative medicine, cancer research, drug dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 157 publications
(183 reference statements)
0
33
0
Order By: Relevance
“…The cell-cell and extracellular matrix established in the 3D culture mimics the specificity in vivo tissue with much more physiological relevance than conventional 2D culture. This feature is the most apparent in studies of cancer cell differentiation and cancer stem cells [32], described as responsible for resistance to treatment, metastasis and recurrence of tumors [2] and tumor models [28,48]. For standardize, the MDA-MD-231 cultivation was established in alginate matrix without change of medium, compared to the same 2D culture.…”
Section: Discussionmentioning
confidence: 99%
“…The cell-cell and extracellular matrix established in the 3D culture mimics the specificity in vivo tissue with much more physiological relevance than conventional 2D culture. This feature is the most apparent in studies of cancer cell differentiation and cancer stem cells [32], described as responsible for resistance to treatment, metastasis and recurrence of tumors [2] and tumor models [28,48]. For standardize, the MDA-MD-231 cultivation was established in alginate matrix without change of medium, compared to the same 2D culture.…”
Section: Discussionmentioning
confidence: 99%
“…To complement analyses provided by human or synthetic CVM models, 3D models that include polymer matrices and multicellular layers -representative of epithelial and stromal layers -have been created to provide a noninvasive and physiologically relevant environment in which to study transport parameters. Although a comprehensive review of available cell culture models may be found in the studies by He et al, 74 hallmark studies relevant to FRT delivery are included in several studies. 44,69,73,74,76,77,84,85 ex vivo transport studies…”
Section: Toward More Realistic In Vitro Systemsmentioning
confidence: 99%
“…Although a comprehensive review of available cell culture models may be found in the studies by He et al, 74 hallmark studies relevant to FRT delivery are included in several studies. 44,69,73,74,76,77,84,85 ex vivo transport studies…”
Section: Toward More Realistic In Vitro Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…To more faithfully represent the mucosal environment, more advanced in vitro systems such as synthetic mucus, 69 undiluted CVM collected from human patients, 13,22,30,31,35,[70][71][72] and 3D cell culture techniques have been developed. 1,28,52,55,[73][74][75][76][77] In addition to utilizing a relevant model to study and obtain transport information, essential physical and chemical properties must be considered to effectively design NPs to navigate the CVM. Depending on whether mucoadhesive or muco-inert properties are preferred, these properties may be tailored to enhance distribution through mucus and to the underlying epithelial and stromal cell layers.…”
Section: B Informing Nanoparticle Design With Empirical Studiesmentioning
confidence: 99%